2020
DOI: 10.1002/cbin.11275
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cellular processes occurring in mucopolysaccharidoses as underestimated pathomechanisms of these diseases

Abstract: Mucopolysaccharidoses (MPS) are a group of genetic disorders belonging to lysosomal storage diseases. They are caused by genetic defects leading to a lack or severe deficiency of activity of one of lysosomal hydrolases involved in degradation of glycosaminoglycans (GAGs). Partially degraded GAGs accumulate in lysosomes, which results in dysfunctions of cells, tissues, and organs. Until recently, it was assumed that GAG accumulation in cells is the major, if not the only, mechanism of pathogenesis in MPS, as GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 46 publications
0
39
0
3
Order By: Relevance
“…In fact, frequent and severe respiratory tract infections were reported as being among characteristic symptoms of enzyme replacement therapy interruption in MPS patients [29–31]. Nevertheless, presented analyses may shed a new light on the MPS course, underlining the importance of modifications of cellular processes, arising from changes in gene expression regulations, in the pathomechanism (as proposed recently [32]), and suggesting that patients suffering from this disease might reveal certain features making them potentially less susceptible to some other diseases.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In fact, frequent and severe respiratory tract infections were reported as being among characteristic symptoms of enzyme replacement therapy interruption in MPS patients [29–31]. Nevertheless, presented analyses may shed a new light on the MPS course, underlining the importance of modifications of cellular processes, arising from changes in gene expression regulations, in the pathomechanism (as proposed recently [32]), and suggesting that patients suffering from this disease might reveal certain features making them potentially less susceptible to some other diseases.…”
Section: Resultsmentioning
confidence: 77%
“…As indicated in recently published reports [12–14], expression of hundreds of genes is changed in MPS cells relative to controls. Specific mechanisms of these regulations remain to be elucidated; however, it was proposed that they reflect secondary and tertiary changes in cellular processes, after primary GAG storage [32]. On the other hand, it has been indicated that severity of MPS symptoms in patients does not simply correlate with GAG levels in organisms of such patients [33].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, not only dysfunctions of cells caused by physical storage of GAG in lysosomes, but also disturbances in cellular processes, caused by dysregulation of different genes are responsible for cellular disorders observed in MPS. Assumptions on importance in secondary and tertiary cellular changes were reported previously (as summarized and discussed recently [40]); however, they were not linked to global changes in genes' expression, and all types of MPS were not investigated in this aspect previously. Our results point to possible molecular mechanisms of both common features of MPS and variability between particular MPS types, indicating the way to study this problem in more detail, to find precise causes of changed gene expression and disturbances of cellular processes.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that the pathogenesis of LSDs is not limited to the primary cause—accumulation of the storage material. Such a hypothesis can be corroborated by recently published results demonstrating dysregulation of expression of hundreds of genes, coding for proteins involved in various cellular processes, in fibroblasts derived from patients suffering from mucopolysaccharidoses [ 51 , 106 , 107 , 108 , 109 , 110 , 111 ].…”
Section: Ferroptosis Disorders As a Mechanism For Pathogenesis Of mentioning
confidence: 62%
“…In fact, changes in ferroptosis efficiency arising from modulation of lysosomal activities have been suggested [ 3 ]. As mentioned in the introduction, various therapeutic strategies for LSD have been tested; however, apart from the non-neuronopathic type of Gaucher disease, no abolition of symptoms could be achieved in severe and neuronopathic forms of these diseases, and only partial improvement could be achieved in milder forms [ 51 , 52 , 53 ].…”
Section: Ferroptosis Disorders As a Mechanism For Pathogenesis Of mentioning
confidence: 99%